EFFECT OF FOLIAR APPLICATION OF POTASSIUM ZINC AND GIBBERELIC ACID ON LEAVES AND PEEL CONTENT OF MINERAL ELEMENTS OF POMEGRANATE CV. SALIMY - & Ali, Jumaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study was carried out during the growing season 2013 in a private orchard in Diyala on pomegranate trees Punica granatum L. cv. Salimy which were nine old years, all trees that chosen had uniform in size and growth were trained on three trunk and planted at 4×4m to study the effect of three levels of potassium sulfate (0, 1500, 3000 mg.K.L-1) and three levels of Zinc (0, 500, and 1000 mg.Z.L-1) and three levels of Gibberellic acid (GA3) (0, 20 and 40 mg.L-1) on leaf and peel content of mineral elements, A factorial experiment with three replicate was carried out according to the (RCBD) using one tree on experimental unit, results Can be summaraized as: Potassium spray led to a significant increase in amount of mineral elements in the leaves, especially concentration 3000 mg.L-1 which achieved an increase in nitrogen, potassium, and zinc, 118.47, 181.00 , and 30.23%, respectively, The same concentration also led to increase elements of calcium and magnesium in the peel of fruit increased by 33.21 and 23.04 respectively, As zinc spray led to in a concentration of 1000 mg.L-1 to an increase of 19.81 and 18.00% of potassium and zinc in the leaves and 7.38% of calcium in the peel, either GA3 to be limited influence a significant to increase zinc in leaves increased by 5.70% and magnesium in the peel by 11.71%, As for Bilateral interactions have mostly affected a significant in qualities of the above except that the greatest influence to appear in the triple overlap to study factors, especially the highest concentrations.